Managing Faculty-Student Collaborations in Research and Authorship - Arthur, Nancy; Anchan, John P.; Este, David; Khanlou, Nazilla; Kwok, Siu-Ming; Mawani, Farah (Canadian Journal of Counselling and Psychotherapy, 2007)
The trend towards multidisciplinary research funding and partnerships brings together researchers with diverse perspectives. However, guidelines for effective supervision in multidisciplinary research are lacking. The New Canadian Children and Youth Study is described as an example of multidisciplinary, multi-site research involving researchers and students in a variety of roles. The benefits and potential difficulties of multiple authorships are reviewed, in light of faculty-student collaborations. Three hypothetical vignettes illustrate research issues and considerations to be made by both faculty and students. Recommendations are outlined for ethical practices in determining authorship contributions in faculty-student research collaborations.